Reorienting the global economy in China's belt and road initiative - Probo Darono Yakti; Siti Rokhmawati Susanto; I Gede Wahyu Wicaksana; Nadya Afdholy; Rumi Azolla Ladiqi (Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
This study aims to examine China's Belt and Road Initiative (BRI) cooperation under the leadership of President Xi Jinping with more than 100 countries in the Indo-Pacific region as a geo-economic order of developmentalism in the Indo-Pacific region to rival the United States (US) with its liberalism. BRI offers developmentalism based on investment-driven economic growth and infrastructure boom. BRI is also a geoeconomic phrase that shows China's geopolitical interest in controlling at least 45 percent of the world economy, whose potential lies along the Silk Road Economic Belt and the Maritime Silk Road. This explanatory research tries to explore further the grand strategy carried out by China in a transformation from the previous leadership era of Mao Zedong, Deng Xiaoping, and Hu Jintao, to Xi Jinping. Then, BRI expanded, as Chinese investment in infrastructure expanded throughout the Indo-Pacific. The data was drawn from a literature study spread across official Chinese government websites (china.gov), journal editors, online media, and e-book provider sites. The findings highlight the declining role of the US in the international world under the leadership of Donald Trump, so that it a strategic opportunity for China to overtake the US. However, the US is no longer the only world hegemon. China is trying to introduce developmentalism as a counter-order to the liberalism that has been promoted by the US.